2019
DOI: 10.3390/catal9100789
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Novel Magnetically Retrievable Nanocomposite with Au Nanocatalysts for Hydration Reaction

Abstract: Developing efficient catalysts with good recyclability is of great importance for its practical applications. In this study, a novel magnetically retrievable nanocomposite (Au-SiO2@Fe3O4-RGO) was synthesized for catalyzing hydration reaction. Active Au nanoparticles are deposited on core-shell SiO2@Fe3O4, which are further supported by a two-dimensional reduced graphene oxide (RGO) platform. The prepared Au-SiO2@Fe3O4-RGO was proven to be efficient as well as recyclable. An excellent catalytic performance, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…13 Among them, the materials prepared by Au and graphene oxide are often tricky because they are challenging to recover. 14 In this paper, by introducing magnetic iron oxide into composites, we hope to obtain materials that can be attracted and controlled using magnets to solve the problem of difficulty in recovering materials to a certain extent.…”
Section: Introductionmentioning
confidence: 99%
“…13 Among them, the materials prepared by Au and graphene oxide are often tricky because they are challenging to recover. 14 In this paper, by introducing magnetic iron oxide into composites, we hope to obtain materials that can be attracted and controlled using magnets to solve the problem of difficulty in recovering materials to a certain extent.…”
Section: Introductionmentioning
confidence: 99%
“…Gold nanoparticles (Au NPs) have attracted more and more attention because of their unique electrical and thermal properties and also, have been widely studied as catalysts due to the strong Lowis acid nature of gold for various reactions [14]. Fe3O4@SiO2@Pd-Au, RGO@Fe3O4@SiO2@Au were used in the synthesis of hydrodechlorination, and hydration, respectively [15][16]. Tsunoyama and coworkers,[17] demonstrated that the catalytic activity of AuNPs is impacted by several factors including particle size and the surface area of nanoparticles which is inversely proportional to the particle size, but directly proportional to the surface area of AuNPs [18][19].…”
Section: Introductionmentioning
confidence: 99%
“…14 Fe 3 O 4 @SiO 2 @Pd-Au and RGO@Fe 3 O 4 @SiO 2 @Au have been used in hydrodechlorination and hydration reactions, respectively. 15,16 Tsunoyama and coworkers 17 demonstrated that the catalytic activity of AuNPs is impacted by several factors, including particle size and the surface area of nanoparticles which is inversely proportional to the particle size, but directly proportional to the surface area of AuNPs. 18,19 Over the past decade, a wide variety of synthetic approaches have been developed to improve the sustainability of organic transformations.…”
Section: Introductionmentioning
confidence: 99%